Outcomes in small children on Berlin Heart EXCOR support: age and body surface area as clinical predictive factors. (8th November 2022) - Rohde, Sofie; Sandica, Eugen; Veen, Kevin; Kraemer, Ulrike S; Thiruchelvam, Timothy; Miera, Oliver; Lopez, Maria L Polo; Sliwka, Joanna; Amodeo, Antonio; Bogers, Ad J J C; de By, Theo M M H
Abstract: OBJECTIVES: The Berlin Heart EXCOR (BHE) offers circulatory support across all paediatric ages. Clinically, the necessary care and the outcomes differ in various age groups. The EUROMACS database was used to study age- and size-related outcomes for this specific device. METHODS: All patients <19 years of age from the EUROMACS database supported with a BHE between 2000 and November 2021 were included. Maximally selected rank statistics were used to determine body surface area (BSA) cut-off values. Multivariable Cox proportional hazard regression using ridge penalization was performed to identify factors associated with outcomes. RESULTS: In total, 303 patients were included [mean age: 2.0 years (interquartile range: 0.6–8.0, males: 48.5%)]. Age and BSA were not significantly associated with mortality ( n = 74, P = 0.684, P = 0.679). Factors associated with a transplant ( n = 175) were age (hazard ratio 1.07, P = 0.006) and aetiology other than congenital heart disease (hazard ratio 1.46, P = 0.020). Recovery rates ( n = 42) were highest in patients with a BSA of <0.53 m 2 (21.8% vs 4.3–7.6% at 1 year, P = 0.00534). Patients with a BSA of ≥0.73 m 2 had a lower risk of early pump thrombosis but a higher risk of early bleeding compared to children with a BSA of <0.73 m 2 . CONCLUSIONS: Mortality rates in Berlin Heart-supported patients cannot be predicted by age or BSA. Recovery rates are remarkably high in the smallest patient category (BSA <0.53 m 2 ). This underscores that the BHE is a viable therapeutic option, even for the smallest and youngest patients. Abstract : Around one-third of the paediatric patients awaiting a cardiac transplant weigh less than 10 kg [1].